CFD Study of Diffuse Ceiling Ventilation through Perforated Ceiling Panels - Alessandro Nocente; Tufan Arslan; Steinar Grynning; Francesco Goia (Energies, 2020)
Diffuse Ceiling Ventilation (DCV) is a promising concept to address internal air quality and thermal comfort requirements in contemporary buildings. Sound-absorbing perforated ceiling panels are common in office rooms and can be used as air diffusers without modifications. The optimization of such systems is not a trivial procedure, and numerical simulation can represent an important tool to carry out this task. Today, most of the numerical studies on DCV are performed using porous medium models and focus on the general system performance rather than on the optimization of the diffuser design. In previous studies, a CFD model was used to optimize the size and distribution of the ceiling perforation. In the study presented in this paper, the results of simulations conducted on a full-scale three-dimensional domain and the performance comparison between a continuous and non-continuous perforation distribution are given. The results show that the non-continuous diffuser design does not disturb the internal comfort and does not introduce a negative effect in the system performance. The different configurations lead to a different air distribution in the room, but in both cases, the velocity magnitude is always well below values leading to draft discomfort.